Metal‐Organic Frameworks Derived Titanium Oxides via Soft Interface Adaptive Transformation. (21st September 2021) - Wang, Jing; Yuan, Ling; Zhang, Chaoqi; Li, Shumin; Wang, Guozhong; Wan, Jingjing; Liu, Chao; Yu, Chengzhong
Abstract: High‐temperature treatment of metal‐organic frameworks (MOFs) is a promising route to prepare a variety of functional materials with diverse applications. However, it is challenging to prepare highly crystalline metal oxides such as TiO2 with controllable structures and morphologies via direct calcination of MOFs. Here, we report a soft interface adaptive transformation strategy for the synthesis of MOFs derived TiO2 nanoparticles with elaborate structures. The soft interface is constructed by coating a thin silica layer on the external surface of Ti‐MOFs with an octahedral morphology. This soft interface can partially adapt to the significant shrinkage and counteract the contraction force during the MOFs‐to‐TiO2 conversion. As a result, TiO2 hollow octahedrons are formed with a concave morphology, high specific surface area, abundant oxygen vacancy sites, and consequently enhanced photocatalytic activity, which cannot be obtained by direct calcination or coating a thick/rigid silica layer. The opposite impact of the interface on MOFs derived metal oxides and carbon materials is further elucidated. This contribution provides new understandings in the synthesis of MOFs derived functional materials. Abstract : A soft interface adaptive transformation strategy is developed for the synthesis of metal‐organic framework derived TiO2 nanoparticles with elaborate structures (e.g., hollow concaved morphology, high surface area, and abundant oxygen vacancies) and enhanced photocatalytic activity.